Hijab in the American workplace: visibility and discrimination. Issue 3 (2nd July 2016) - Robinson, Rebecca S.
Abstract: While the initial purpose of this article was to outline online collective action (OCA) towards promoting the rights of hijab-wearing Muslim women in the workplace, it became apparent that there were substantial impediments to this solidarity. Thus, the bulk of it takes up these obstacles, arguing that American hijabis face structural discrimination and Muslims in the United States are subjected to heightened discrimination when they are highly visible to the mainstream culture. This article reviews two cases of workplace discrimination against hijabis and the reactions to these incidents on the Huffington Post, Los Angeles Times, and hijab-oriented blogs. Findings indicate that intolerance of Muslims is prevalent across various political affiliations and apprehension associated with hijabi rights could be related to the perceived decline of white privilege. The analysis also demonstrates that there may be impediments to solidarity with hijabi rights within Muslim communities due to disagreements on the Qur'anic mandate of modesty, divergent perspectives on how Muslims can best promote their rights and ensure their safety, and misunderstandings related to the rights guaranteed under reasonable accommodation. Despite the various obstacles to solidarity with hijabis, the article traces various forms of OCA at local, national and international levels that were encountered on social media platforms.